EDUKASI PROGRAM “CERIA”: CEGAH THALASEMIA REMAJA INDONESIA - Yanti Hemayanti; Iwan Shalahuddin (Universitas Mataram, 2026)
Thalassemia is one of the genetic diseases with a relatively high prevalence in Indonesia, with approximately 5–10% of the population being carriers. The lack of knowledge among adolescents about thalassemia and the importance of early screening poses a serious challenge to prevention efforts. According to data from the World Health Organization (WHO), approximately 5% of the world's population carries the thalassemia trait, and in Indonesia, the prevalence of thalassemia carriers ranges from 3-10% depending on the region. Therefore, innovative educational programs are needed, one of which is through CERIA (Preventing Indonesian Adolescent Thalassemia). This program aims to increase adolescents' knowledge, attitudes, and awareness regarding thalassemia, and to promote preventive behaviors thru genetic screening and healthy marriages. The activities were conducted offline thru interactive outreach, small group discussions, and digital educational media such as videos and infographics. The participants are high school students selected through purposive sampling. Evaluation was conducted through pre-tests and post-tests to measure knowledge improvement and attitude changes. The CERIA program is able to improve participants' understanding of the causes, risk factors, impact, and prevention methods for thalassemia. There was an increase in the average knowledge scores and positive attitudes toward genetic screening and the role of adolescents in preventing this disease. The average pre-test score obtained by the students was 56.67-83.00. There was an average increase of 46.47% from the pre-test to the post-test. This value reflects the students' initial level of understanding before receiving the learning materials or activities provided. Participants also demonstrated a commitment to becoming peer educators in the school environment. The CERIA education program is effective in improving adolescent health literacy about thalassemia and has the potential to support the national thalassemia prevention program in Indonesia. The implementation of similar programs needs to be expanded by involving schools, healthcare workers, and government support to strengthen promotional and preventive efforts.